Influence of Equimolar Doses of Beetroot Juice and Sodium Nitrate on Time Trial Performance in Handcycling - Joelle Leonie Flueck (Nutrients, 2019)
This study aimed to investigate the influence of a single dose of either beetroot juice (BR) or sodium nitrate (NIT) on performance in a 10 km handcycling time trial (TT) in able-bodied individuals and paracyclists. In total, 14 able-bodied individuals [mean ± SD; age: 28 ± 7 years, height: 183 ± 5 cm, body mass (BM): 82 ± 9 kg, peak oxygen consumption (VO2peak): 33.9 ± 4.2 mL/min/kg] and eight paracyclists (age: 40 ± 11 years, height: 176 ± 9cm, BM: 65 ± 9 kg, VO2peak: 38.6 ± 10.5 mL/min/kg) participated in the study. All participants had to perform three TT on different days, receiving either 6 mmol nitrate as BR or NIT or water as a placebo. Time-to-complete the TT, power output (PO), as well as oxygen uptake (VO2) were measured. No significant differences in time-to-complete the TT were found between the three interventions in able-bodied individuals (p = 0.80) or in paracyclists (p = 0.61). Furthermore, VO2 was not significantly changed after the ingestion of BR or NIT in either group (p < 0.05). The PO to VO2 ratio was significantly higher in some kilometers of the TT in able-bodied individuals (p < 0.05). The ingestion of BR or NIT did not increase handcycling performance in able-bodied individuals or in paracyclists.